(untitled) - Lussier, Robert N. (Boston, 2010)
Offers a three-pronged approach: an understanding of human relations/ organizational behavior concepts; the application of HR/OB concepts for critical thinking in the business world; and, the development of HR/OB skills. This book is suitable for professors who want to incorporate activities and exercises into the classroom.
Keywords: Organizational behavior,Interpersonal relations,Ứng xử trong tổ chức,Mối quan hệ giữa các cá nhân